2017
DOI: 10.1128/jvi.00873-17
|View full text |Cite
|
Sign up to set email alerts
|

Cysteines and N-Glycosylation Sites Conserved among All Alphaherpesviruses Regulate Membrane Fusion in Herpes Simplex Virus 1 Infection

Abstract: Neurotropism is a defining characteristic of alphaherpesvirus pathogenicity. Glycoprotein K (gK) is a conserved virion glycoprotein of all alphaherpesviruses that is not found in other herpesvirus subfamilies. The extracellular amino terminus of gK has been shown to be important to the ability of the prototypic alphaherpesvirus herpes simplex virus 1 (HSV-1) to enter neurons via axonal termini. Here, we determined the role of the two conserved N-linked glycosylation (N48 and N58) sites of gK in virus-induced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…The VC2 virus harbors mutations in two of its viral envelope proteins: glycoprotein K (gK) and UL20 (36). VC2 virus was grown and titrated in Vero cells (ATCC), as described previously (65). and B16F10n-1 cells were engrafted orthotopically in the dermis of the dorsal left dorsal pinna, as previously reported (66).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The VC2 virus harbors mutations in two of its viral envelope proteins: glycoprotein K (gK) and UL20 (36). VC2 virus was grown and titrated in Vero cells (ATCC), as described previously (65). and B16F10n-1 cells were engrafted orthotopically in the dermis of the dorsal left dorsal pinna, as previously reported (66).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Studies by the same group showed that both gK and PlLRα (paired immunoglobulin–like type 2 receptor α) bound gB in infected cells and that the association between gB-PILRα protein complex regulates membrane fusion of virus and the host cell which aids in virus penetration (75). Along with the role of amino terminus of gK in virus entry, a recent study described the role of two conserved N-linked glycosylation sites (N48 and N58) of gK in virus-induced cell fusion and replication (76). Mutation at N58 to alanine (N58A) resulted in extensive virus-induced cell fusion.…”
Section: Gk and Virus Entrymentioning
confidence: 99%
“…Mutation at N58 to alanine (N58A) resulted in extensive virus-induced cell fusion. The same group showed that mutation of cysteine residues within the amino terminus of gK, C37, and C114, led to significant reduction in virus production (76). In addition, gK plays a vital part in the recruitment of other viral glycoproteins into intracellular virus assembly.…”
Section: Gk and Virus Entrymentioning
confidence: 99%
“…Alternatively, it is feasible that hypoglycosylated particles adhere or fuse with Vero cells, but that a downstream step necessary for viral replication or distribution fails. For example, HSV-1 induced cell fusion and syncytia formation increase with gK hypoglycosylation because of point mutation (13). NGI-1 treatment of HEK293 lines might similarly yield hypoglycosylated HSV-1 particles that infect Vero cells and replicate, but instead of causing cell death, the resultant nascent particles might lead to syncytia that do not result in typical plaques.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with gC and gD, an N-glycan on envelope glycoprotein gK is important for HSV-1 pathogenesis because gK must be properly N-glycosylated for cytopathic effects associated with plaque formation. Mutation of gK, to prevent glycosylation of Asn 58 , leads to obscured plaques and greater syncytia formation on Vero cell monolayers (13). In summary, there is a substantial body of evidence supporting the importance of N-glycans of envelope proteins in HSV-1 function, but potential roles may be host cell and context dependent.…”
mentioning
confidence: 98%